TRANSFORMASI FOTO MANEKIN MENJADI FOTO MODEL MENGGUNAKAN AI (Jurnal Da Moda, 2024)
The use of AI has revolutionized processes in various industries, including in the fashion industry. This article discusses how to transform a photo of a clothing mannequin into a realistic AI model. This article was compiled through trial using weshop and photoshop applications. The result: 1) Detail prompt; 2) Mannequin photo or pose reference: 3) Mannequin type (half body, full body, static, movable); 4) The placement of mannequins (indoor or outdoor) greatly influences AI results. Business-wise, these AI images can be used for clothing presentations, or as an alternative to photos of social media content, providing an unlimited variety of models. This article is expected to provide a brief overview of the benefits of AI for clothing photos.